Suomi‐NPP CrIS radiometric calibration uncertainty. Issue 18 (19th September 2013) - Tobin, David; Revercomb, Henry; Knuteson, Robert; Taylor, Joe; Best, Fred; Borg, Lori; DeSlover, Dan; Martin, Graeme; Buijs, Henry; Esplin, Mark; Glumb, Ronald; Han, Yong; et al.
Abstract [1] The Cross‐track Infrared Sounder (CrIS) is the high spectral resolution spectroradiometer on the Suomi National Polar‐Orbiting Partnership (NPP) satellite, providing operational observations of top‐of‐atmosphere thermal infrared radiance spectra for weather and climate applications. This paper describes the CrIS radiometric calibration uncertainty based on prelaunch and on‐orbit efforts to estimate calibration parameter uncertainties, and provides example results of recent postlaunch validation efforts to assess the predicted uncertainty. Prelaunch radiometric uncertainty (RU) estimates computed for the laboratory test environment are less than 0.2 K 3 sigma for blackbody scene temperatures above 250 K, with primary uncertainty contributions from the calibration blackbody temperature, calibration blackbody reflected radiance terms, and detector nonlinearity. Variability of the prelaunch RU among the longwave band detectors and midwave band detectors is due to different levels of detector nonlinearity. A methodology for on‐orbit adjustment of nonlinearity correction parameters to reduce the overall contribution to RU and to reduce field of view (FOV)‐to‐FOV variability is described. The resulting on‐orbit RU estimates for Earth view spectra are less than 0.2 K 3 sigma in the midwave and shortwave bands, and less than 0.3 K 3 sigma in the longwave band. Postlaunch validation efforts to assess the radiometric calibration of CrIS are underway; validation results to date indicate that the on‐orbit RU estimates are representative. CrIS radiance products are expected to reach "Validated" status in early 2014.